A comparative study of different methods to calculate degrees of composite action for insulated concrete sandwich panels. (1st June 2020) - Chen, An; Yossef, Mostafa; Hopkins, Paul
Highlights: Comparative study of three widely used methods to calculate the degree of composite action. 3-D Finite Element model accounts for material nonlinear behavior, concrete damage plasticity and prestressing force. Innovative method to simulate shear connectors behavior in 3-D FE model using connector elements and coupling. Abstract: Precast concrete sandwich wall panels consist of two outer wythes of precast concrete separated by a middle layer of insulation. In recent years, Fiber-Reinforced Polymer (FRP) shear connectors have been increasingly used since they have lower thermal conductivity compared to traditional steel shear connectors, which can significantly reduce thermal bridging. However, FRP shear connectors have lower stiffness, resulting in partial Degree of Composite Action (DCA), which is an important parameter to describe the structural behavior of the panels. Different methods have been proposed to calculate DCAs, including displacement method, strain method, and load method. This paper will compare and evaluate the effectiveness of these methods. A bending test was conducted on a full size of 7 m × 3 m, precast, prestressed insulated concrete sandwich panel with FRP shear connectors. A non-linear Finite Element (FE) model is created, where good correlations can be achieved between the test and FE results. The FE model is further employed to conduct a parametric study by varying the stiffness of the shear connectors. DCAs for different stiffnesses are calculated using the aforementioned three methods and the applicability and limitation of each method are investigated.